Naturae cognoscere causas... Schools Endeavour Educational Materials - Marciniak, Katarzyna; Ryba, Janusz; Strycharczyk, Barbara; Strycharczyk, Olga; Wojciechowska, Anna (University of Warsaw Press, 2021)
The book prepared by students, working under tutorship of their teachers, from three Polish high schools, on the theme of Classical Antiquity and Nature, within the Our Mythical Childhood Project. Texts: Teachers and Students from the Schools involved in the Project: Janusz Ryba and the Students from Bartłomiej Nowodworski I High School in Kraków, Barbara Strycharczyk, Agata Płotczyk, Anna Łukomska, and the Students from "Strumienie" High School in Józefów, Anna Wojciechowska and the Students from Mikołaj Rej XI High School in Warsaw, and Katarzyna Marciniak, Faculty of "Artes Liberales", University of Warsaw. The publication appears in the series "OBTA Studies in Classical Reception" - as already the second volume in the educational cycle ("Educational Materials"), after ""De viris mulieribusque illustribus"", prepared in 2019 by the students participating in the Our Mythical History stage. Both volumes are in dialogue with each other by showing the interests of the young people and by pointing to the chances offered by an education in the spirit of artes liberales with the method of interdisciplinary team projects. This volume is in a dialogue also with other elements of the Our Mythical Childhood programme: the third edition of the video competition for elementary and high-school students ""Antiquity-Camera-Action!"", dedicated to the theme of ecology, and with the conference summing up the Nature stage. Katarzyna Marciniak, from ""A Garden in the Library, or How the Classics Can Lead Us Back to Nature"